Sistem Komunikasi Indonesia: Suatu Proses Sosial, Budaya, dan Politik - Rafinita Aditia (Connected: Jurnal Ilmu Komunikasi, 2021)
To be in the era of the communication revolution as it is now, the Indonesian communication system has gone through impractical stages. Various communication developments have led Indonesia to a process that is updated day by day. Each communication revolution has a different span of time, it takes centuries for the system to progress one stage. This research will explain how the Indonesian Communication System is viewed as a social, cultural, and political process. The research approach used in this research is a qualitative approach with a library research method. The results show that the Indonesian communication system as a social process is an integral part of society. The Indonesian communication system as a cultural process is undeniably the objectivation between culture and communication. And the Indonesian communication system as a political process explains that communication plays a role in connecting parts of the political system.